Plasma pTau181 is associated with subjective cognitive concerns but not objective cognitive decline or structural brain integrity measures in midlife - Ashleigh Barrett-Young; Erin E. Cawston; Brigid Ryan; Wickliffe C. Abraham; Antony Ambler; Tim Anderson; Kirsten Cheyne; Elizabeth Goodin; Sean Hogan; Renate M. Houts; David Ireland; Annchen R. Knodt; et al. (GeroScience, 2026)
Although plasma pTau181 has been shown to accurately discriminate patients with Alzheimer’s disease from healthy older adults, there are few studies of plasma biomarkers among middle-aged populations. Given the potential utility of plasma AD biomarkers such as pTau181 in screening for disease risk, examining pTau181 in a middle-aged cohort without AD is important for future implementation. The objectives of this study were to characterise plasma pTau181 in a middle-aged birth cohort aged 45 years and to investigate associations with early indicators of dementia risk. Participants were members of the Dunedin Multidisciplinary Health and Development Study, a longitudinal study of 1037 people born in New Zealand in 1972–1973. Plasma pTau181, self-reported cognitive concerns, MRI-based brain structure, and DunedinPACE (an epigenetic biomarker of biological ageing) were measured at age 45; cognition was measured in childhood and age 45. Plasma pTau181 concentrations at age 45 ( n = 854, 49% female) were associated with self-reported cognitive concerns (β = 0.09, p = .008); however, no significant associations were observed with objective cognitive decline, worse structural brain integrity, or biological ageing. Higher plasma pTau181 was associated with self-reported cognitive concerns at age 45, but not objective AD-related measures. The association of plasma pTau181 and self-reported cognitive concerns in this cohort suggests that AD pathology may begin to accumulate by age 45 and may be associated with subtle changes in cognition that are not at objectively measurable levels. Graphical Abstract

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Identification of bovine genotypes conferring diminished susceptibility to salmonellosis and colonization by Salmonella and E. coli O157:H7 - Kristi L. Anderson; Duane K. Ramsey; Tim A. Day; Steve A. Carlson (Veterinary Microbiology, 2025)

Behavioural effects of oral cannabidiol (CBD) treatment in the superoxide dismutase 1 G93 A (SOD1G93 A) mouse model of amyotrophic lateral sclerosis - Sandip Ghimire; Fabian Kreilaus; Rossana Rosa Porto; Lyndsey L. Anderson; Justin J. Yerbury; Jonathon C. Arnold; Tim Karl (Psychopharmacology, 2025)
Background Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease affecting voluntary muscle movement as well as cognitive and other behavioural domains at later disease stages. No effective treatment for ALS is currently available. Elevated neuroinflammation, oxidative stress and alterations to the endocannabinoid system are evident in ALS. The phytocannabinoid cannabidiol (CBD) has anti-inflammatory and anti-oxidant properties. Thus, we evaluated the remedial effects of chronic oral cannabidiol (CBD) treatment on ALS-relevant behavioural domains in the copper-zinc superoxide dismutase 1 ( SOD1 ) mouse model of ALS that carries a G93A mutation ( SOD1 G93A ). Methods Male and female SOD1 G93A and wild type-like (WT) littermates were fed either a control (CHOW) or CBD-enriched chow diet (equivalent to a dose of 36 mg/kg per day) beginning from 10 weeks of age. Bodyweight and motor performance were recorded weekly from 11 to 19 weeks and open field behaviours at 12 and 18 weeks. Mice were also tested for prepulse inhibition (PPI), social behaviours, as well as fear-associated memory. Results CBD treatment ameliorated the bodyweight loss in female SOD1 G93A mice, tended to reinstate sociability in SOD1 G93A males, strengthened social recognition memory in SOD1 G93A females, and improved the PPI response in younger SOD1 G93A females at higher prepulse intensities. CBD had no effect on motor impairments but instead reversed the anxiolytic-like phenotype of 12-week-old male SOD1 G93A mice and decreased the acoustic startle response and strengthened cue freezing in male mice. Conclusion Thus, the current remedial oral dose of CBD delayed disease progression (inferred by bodyweight) in both male and female mice and improve specific cognitive deficits of SOD1 G93A mice in a sex specific manner without altering the motor phenotype.

Pre-existing ground cracks as lava flow pathways at Kīlauea in 2014 - Tim R. Orr; Edward W. Llewellin; Kyle R. Anderson; Matthew R. Patrick (Bulletin of Volcanology, 2024)

What factors influence the rediscovery of lost tetrapod species? - Tim Lindken; Christopher V. Anderson; Daniel Ariano‐Sánchez; Goni Barki; Christina Biggs; Philip Bowles; Ramamoorthi Chaitanya; Drew T. Cronin; Sonja C. Jähnig; Jonathan M. Jeschke; Rosalind J. Kennerley; Thomas E. Lacher; et al. (Global Change Biology, 2024)
We created a database of lost and rediscovered tetrapod species, identified patterns in their distribution and factors influencing rediscovery. Tetrapod species are being lost at a faster rate than they are being rediscovered, due to slowing rates of rediscovery for amphibians, birds and mammals, and rapid rates of loss for reptiles. Finding lost species and preventing future losses should therefore be a conservation priority. By comparing the taxonomic and spatial distribution of lost and rediscovered tetrapod species, we have identified regions and taxa with many lost species in comparison to those that have been rediscovered—our results may help to prioritise search effort to find them. By identifying factors that influence rediscovery, we have improved our ability to broadly distinguish the types of species that are likely to be found from those that are not (because they are likely to be extinct). Some lost species, particularly those that are small and perceived to be uncharismatic, may have been neglected in terms of conservation effort, and other lost species may be hard to find due to their intrinsic characteristics and the characteristics of the environments they occupy (e.g. nocturnal species, fossorial species and species occupying habitats that are more difficult to survey such as wetlands). These lost species may genuinely await rediscovery. However, other lost species that possess characteristics associated with rediscovery (e.g. large species) and that are also associated with factors that negatively influence rediscovery (e.g. those occupying small islands) are more likely to be extinct. Our results may foster pragmatic search protocols that prioritise lost species likely to still exist.

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand indicate biodiversity change - Irene Middleton; Malcolm Francis; J. David Aguirre; Carl Struthers; Thomas Trnski; Clinton Duffy; John Anderson; Mary Carney; Nathan Cox; Stephen Hemstalk; Blair Herbert; Craig Johnston; et al. (Journal of Biogeography, 2023)
Aim Climate change is driving biogeographic change globally, including poleward range shifts of species and the increasing abundance of rare species. We examine spatiotemporal patterns in the occurrences of tropical, subtropical and rare marine fishes in Aotearoa New Zealand to determine whether biodiversity change is occurring in this temperate region and to set a baseline for future monitoring of climate change impacts. Location Aotearoa New Zealand (NZ). Taxon Marine fishes. Methods We consolidated 100 years of unpublished records and citizen science sightings of tropical, subtropical and rare fishes to develop a focal species database for NZ. Using hotspot analysis, we identified geographic locations where the occurrence and diversity of focal species is greater than expected. We examine the spatiotemporal variation in hotspots by focal species lifestage, habitat and taxonomic family. Results Focal species occurrences and diversity in NZ have increased. We present 17 new‐to‐NZ marine fish species, and a new‐to‐NZ family. Focal species now account for 6.5% of pelagic fishes and 17.3% of benthic fishes in NZ. The northeast of the North Island (Te Ika‐a‐Māui) was a consistent hotspot of focal species occurrences and diversity. Hotspots of mature and pelagic fish occurrences appeared further south than juvenile and benthic species occurrences. Families with tropical affinities (Labridae and Pomacentridae) were restricted to northeastern NZ whereas hotspots of families with temperate affinities (i.e. Cheilodactylidae) extended into the South Island (Te Waipounamu). Main Conclusions Tropical, subtropical and rare fishes are a major component of the fish biodiversity in temperate NZ, and their occurrences and diversity has increased over the past half‐century. Northeastern NZ consistently has the highest occurrence rate and diversity of warmer‐water fishes. Our study demonstrates the value in consolidating citizen scientist observations to detect biodiversity change, and to inform current baselines and future monitoring of climate‐related biodiversity change.

Ecological consequences of historic moorland ‘improvement’ - Francis M. Rowney; Ralph M. Fyfe; Philip Anderson; Robert Barnett; William Blake; Tim Daley; Katie Head; Alison MacLeod; Ian Matthews; David N. Smith (Biodiversity and Conservation, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Earth Observation for agricultural drought monitoring in the Pannonian Basin (southeastern Europe): current state and future directions - Laura Crocetti; Matthias Forkel; Milan Fischer; František Jurečka; Aleš Grlj; Andreas Salentinig; Miroslav Trnka; Martha Anderson; Wai-Tim Ng; Žiga Kokalj; Andreea Bucur; Wouter Dorigo (Regional Environmental Change, 2020)
The Pannonian Basin in southeastern Europe is heavily used for rain-fed agriculture. The region experienced several droughts in the last years, causing major yield losses. Ongoing climate change, characterised by increasing temperatures and potential evapotranspiration, and by changes in precipitation distribution will likely increase the frequency and intensity of drought episodes in the future. Hence, ongoing monitoring of droughts and estimation of their impact on agriculture is necessary to adapt agricultural practices to changing weather and climate extremes. Several regional initiatives, projects and online tools have been established to facilitate drought monitoring and management in the Pannonian Basin. However, reliable systems to forecast potential drought impacts on plant productivity and agricultural yields at monthly to seasonal scales are only in their infancy, as plant response to climatic extremes is still poorly understood. With the increasing availability of high-resolution and long-term Earth Observation (EO) data and recent progress in machine learning and artificial intelligence, further improvements in drought monitoring and impact prediction capacities are expected. Here we review the current state of drought monitoring in the Pannonian Basin, identify EO-based variables to potentially improve regional drought impact monitoring and outline future perspectives for seasonal forecasts of drought impacts on agriculture.

Uncertainty in geomorphological responses to climate change - Stephan Harrison; Tim Mighall; David A. Stainforth; Philip Allen; Mark Macklin; Edward Anderson; Jasper Knight; Dmitri Mauquoy; David Passmore; Brice Rea; Matteo Spagnolo; Sarah Shannon (Climatic Change, 2019)

Genetic distinctiveness of brown pelicans (Pelecanus occidentalis) from the Galápagos Islands compared to continental North America - Scott A. Taylor; Melissa Jenkins; Meera Manghani; Tim Birt; David J. Anderson; Gustavo Jiménez-Uzcátegui; Vicki Friesen (Conservation Genetics, 2018)

Publishing social science research in Conservation Biology to move beyond biology - Tara L. Teel; Christopher B. Anderson; Mark A. Burgman; Joshua Cinner; Douglas Clark; Rodrigo A. Estévez; Julia P.G. Jones; Tim R. McClanahan; Mark S. Reed; Chris Sandbrook; Freya A.V. St. John (Conservation Biology, 2018)

Qualitative analysis of Parkinson’s disease information on social media: the case of YouTube™ - Ibrahim Saleh Al-Busaidi; Tim J. Anderson; Yassar Alamri (EPMA Journal, 2017)
Introduction There is a paucity of data pertaining to the usefulness of information presented on social media platforms on chronic neuropsychiatric conditions such as Parkinson’s disease (PD). The aim of this study was to examine the quality of YouTube™ videos that deliver general information on PD and the availability and design of instructional videos addressing the caregiving role in PD. Methods YouTube™ was searched using the keyword “Parkinson’s disease” for relevant videos. Videos were assessed for usefulness and accuracy based on pre-defined criteria. Data on video characteristics including total viewership, duration, ratings, and source of videos were collated. Instructional PD videos that addressed the role of caregivers were examined closely for the design and scope of instructional content. Results A total of 100 videos met the inclusion criteria. Just under a third of videos (28%) was uploaded by trusted academic organisations. Overall, 15% of PD videos were found to be somewhat useful and only 4% were assessed as providing very useful PD information; 3% of surveyed videos were misleading. The mean number of video views (regardless of video source) was not significantly different between the different video ratings ( p = 0.86). Although personal videos trended towards being less useful than videos from academic organisations, this association was not statistically significant ( p = 0.13). Conclusion To our knowledge, this is the first study to assess the usefulness of PD information on the largest video-sharing website, YouTube™. In general, the overall quality of information presented in the videos screened was mediocre. Viewership of accurate vs. misleading information was, however, very similar. Therefore, healthcare providers should direct PD patients and their families to the resources that provide reliable and accurate information.

Shelf–Basin interaction along the East Siberian Sea - Leif G. Anderson; Göran Björk; Ola Holby; Sara Jutterström; Carl Magnus Mörth; Matt O'Regan; Christof Pearce; Igor Semiletov; Christian Stranne; Tim Stöven; Toste Tanhua; Adam Ulfsbo; et al. (Ocean Science, 2017)
Extensive biogeochemical transformation of organic matter takes place in the shallow continental shelf seas of Siberia. This, in combination with brine production from sea-ice formation, results in cold bottom waters with relatively high salinity and nutrient concentrations, as well as low oxygen and pH levels. Data from the SWERUS-C3 expedition with icebreaker Oden, from July to September 2014, show the distribution of such nutrient-rich, cold bottom waters along the continental margin from about 140 to 180° E. The water with maximum nutrient concentration, classically named the upper halocline, is absent over the Lomonosov Ridge at 140° E, while it appears in the Makarov Basin at 150° E and intensifies further eastwards. At the intercept between the Mendeleev Ridge and the East Siberian continental shelf slope, the nutrient maximum is still intense, but distributed across a larger depth interval. The nutrient-rich water is found here at salinities of up to ∼ 34.5, i.e. in the water classically named lower halocline. East of 170° E transient tracers show significantly less ventilated waters below about 150 m water depth. This likely results from a local isolation of waters over the Chukchi Abyssal Plain as the boundary current from the west is steered away from this area by the bathymetry of the Mendeleev Ridge. The water with salinities of ∼ 34.5 has high nutrients and low oxygen concentrations as well as low pH, typically indicating decay of organic matter. A deficit in nitrate relative to phosphate suggests that this process partly occurs under hypoxia. We conclude that the high nutrient water with salinity ∼ 34.5 are formed on the shelf slope in the Mendeleev Ridge region from interior basin water that is trapped for enough time to attain its signature through interaction with the sediment.

Increasing hydrologic variability threatens depleted anadromous fish populations - Eric J. Ward; Joseph H. Anderson; Tim J. Beechie; George R. Pess; Michael J. Ford (Global Change Biology, 2015)
Predicting effects of climate change on species and ecosystems depend on understanding responses to shifts in means (such as trends in global temperatures), but also shifts in climate variability. To evaluate potential responses of anadromous fish populations to an increasingly variable environment, we performed a hierarchical analysis of 21 Chinook salmon populations from the Pacific Northwest, examining support for changes in river flows and flow variability on population growth. More than half of the rivers analyzed have already experienced significant increases in flow variability over the last 60 years, and this study shows that this increase in variability in freshwater flows has a more negative effect than any other climate signal included in our model. Climate change models predict that this region will experience warmer winters and more variable flows, which may limit the ability of these populations to recover.

What is the impact of systematically missing exposure data on air pollution health effect estimates? - Evangelia Samoli; Roger D. Peng; Tim Ramsay; Giota Touloumi; Francesca Dominici; Richard W. Atkinson; Antonella Zanobetti; Alain Le Tertre; H. Ross Anderson; Joel Schwartz; Aaron Cohen; Daniel Krewski; et al. (Air Quality, Atmosphere & Health, 2014)

Hive‐stored pollen of honey bees: many lines of evidence are consistent with pollen preservation, not nutrient conversion - Kirk E. Anderson; Mark J. Carroll; Tim Sheehan; Brendon M. Mott; Patrick Maes; Vanessa Corby‐Harris (Molecular Ecology, 2014)
Honey bee hives are filled with stored pollen, honey, plant resins and wax, all antimicrobial to differing degrees. Stored pollen is the nutritionally rich currency used for colony growth and consists of 40–50% simple sugars. Many studies speculate that prior to consumption by bees, stored pollen undergoes long‐term nutrient conversion, becoming more nutritious ‘bee bread’ as microbes predigest the pollen. We quantified both structural and functional aspects associated with this hypothesis using behavioural assays, bacterial plate counts, microscopy and 454 amplicon sequencing of the 16S rRNA gene from both newly collected and hive‐stored pollen. We found that bees preferentially consume fresh pollen stored for 96 h. The estimated microbe to pollen grain surface area ratio was 1:1 000 000 indicating a negligible effect of microbial metabolism on hive‐stored pollen. Consistent with these findings, hive‐stored pollen grains did not appear compromised according to microscopy. Based on year round 454 amplicon sequencing, bacterial communities of newly collected and hive‐stored pollen did not differ, indicating the lack of an emergent microbial community co‐evolved to digest stored pollen. In accord with previous culturing and 16S cloning, acid resistant and osmotolerant bacteria like Lactobacillus kunkeei were found in greatest abundance in stored pollen, consistent with the harsh character of this microenvironment. We conclude that stored pollen is not evolved for microbially mediated nutrient conversion, but is a preservative environment due primarily to added honey, nectar, bee secretions and properties of pollen itself.

Achieving consistency in life cycle assessment practice within the European construction sector: the role of the EeBGuide InfoHub - Sébastien Lasvaux; Johannes Gantner; Bastian Wittstock; Manuel Bazzana; Nicoleta Schiopu; Tom Saunders; Cristina Gazulla; Jo Ann Mundy; Christer Sjöström; Pere Fullana-i-Palmer; Tim Barrow-Williams; Anna Braune; et al. (The International Journal of Life Cycle Assessment, 2014)

Regional signatures of plant response to drought and elevated temperature across a desert ecosystem - Seth M. Munson; Esteban H. Muldavin; Jayne Belnap; Debra P. C. Peters; John P. Anderson; M. Hildegard Reiser; Kirsten Gallo; Alicia Melgoza-Castillo; Jeffrey E. Herrick; Tim A. Christiansen (Ecology, 2013)
The performance of many desert plant species in North America may decline with the warmer and drier conditions predicted by climate change models, thereby accelerating land degradation and reducing ecosystem productivity. We paired repeat measurements of plant canopy cover with climate at multiple sites across the Chihuahuan Desert over the last century to determine which plant species and functional types may be the most sensitive to climate change. We found that the dominant perennial grass, Bouteloua eriopoda , and species richness had nonlinear responses to summer precipitation, decreasing more in dry summers than increasing with wet summers. Dominant shrub species responded differently to the seasonality of precipitation and drought, but winter precipitation best explained changes in the cover of woody vegetation in upland grasslands and may contribute to woody‐plant encroachment that is widespread throughout the southwestern United States and northern Mexico. Temperature explained additional variability of changes in cover of dominant and subdominant plant species. Using a novel empirically based approach we identified “climate pivot points” that were indicative of shifts from increasing to decreasing plant cover over a range of climatic conditions. Reductions in cover of annual and several perennial plant species, in addition to declines in species richness below the long‐term summer precipitation mean across plant communities, indicate a decrease in the productivity for all but the most drought‐tolerant perennial grasses and shrubs in the Chihuahuan Desert. Overall, our regional synthesis of long‐term data provides a robust foundation for forecasting future shifts in the composition and structure of plant assemblages in the largest North American warm desert.

Acute effects of ambient ozone on mortality in Europe and North America: results from the APHENA study - Roger D. Peng; Evangelia Samoli; Luu Pham; Francesca Dominici; Giota Touloumi; Tim Ramsay; Richard T. Burnett; Daniel Krewski; Alain Le Tertre; Aaron Cohen; Richard W. Atkinson; H. Ross Anderson; et al. (Air Quality, Atmosphere & Health, 2013)

Population genetic correlates of declining transmission in a human pathogen - Standwell C. Nkhoma; Shalini Nair; Salma Al‐Saai; Elizabeth Ashley; Rose McGready; Aung P. Phyo; François Nosten; Tim J. C. Anderson (Molecular Ecology, 2013)
Pathogen control programs provide a valuable, but rarely exploited, opportunity to directly examine the relationship between population decline and population genetics. We investigated the impact of an ~12‐fold decline in transmission on the population genetics of P lasmodium falciparum infections ( n = 1731) sampled from four clinics on the T hai– B urma border over 10 years and genotyped using 96 genome‐wide SNP s. The most striking associated genetic change was a reduction in the frequency of infections containing multiple parasite genotypes from 63% in 2001 to 14% in 2010 ( P = 3 × 10 −15 ). Two measures of the clonal composition of populations (genotypic richness and the β‐parameter of the Pareto distribution) declined over time as more people were infected by parasites with identical multilocus genotypes, consistent with increased selfing and a reduction in the rate at which multilocus genotypes are broken apart by recombination. We predicted that the reduction in transmission, multiple clone carriage and outbreeding would be mirrored by an increased influence of genetic drift. However, geographical differentiation and expected heterozygosity remained stable across the sampling period. Furthermore, N e estimates derived from allele frequencies fluctuation between years remained high (582 to ∞) and showed no downward trend. These results demonstrate how genetic data can compliment epidemiological assessments of infectious disease control programs. The temporal changes in a single declining population parallel to those seen in comparisons of parasite genetics in regions of differing endemicity, strongly supporting the notion that reduced opportunity for outbreeding is the key driver of these patterns.

Electrocorticographic (ECoG) correlates of human arm movements - Nicholas R. Anderson; Tim Blakely; Gerwin Schalk; Eric C. Leuthardt; Daniel W. Moran (Experimental Brain Research, 2012)

Memory-guided saccades in Parkinson’s disease: long delays can improve performance - Campbell J. Le Heron; Michael R. MacAskill; Tim J. Anderson (Experimental Brain Research, 2005)

Digital Forestry: A White Paper - Guang Zhao; Guofan Shao; Keith M. Reynolds; Michael C. Wimberly; Tim Warner; John W. Moser; Keith Rennolls; Steen Magnussen; Michael Köhl; Hans-Erik Anderson; Guillermo A. Mendoza; Limin Dai; et al. (Journal of Forestry, 2005)
Digital Forestry has been proposed as ”the science, technology, and art of systematically acquiring, integrating, analyzing, and applying digital information to support sustainable forests.” Although rooted in traditional forestry disciplines, Digital Forestry draws from a host of other fields that, in the past few decades, have become important for implementing the concept of forest ecosystem management and the principle of sustainable forestry. Digital Forestry is a framework that links all facets of forestry information at local, national, and global levels through an organized digital network. It is anticipated that a new set of principles will be established when practicing Digital Forestry concept for the evolution of forestry education, research, and practices as the 21st century unfolds.

The transformation of anthers in the msca1 mutant of maize - Raj Chaubal; John R. Anderson; Mary R. Trimnell; Tim W. Fox; Marc C. Albertsen; Patricia Bedinger (Planta, 2003)

Using Chorioallantoic Membranes for Non-lethal Assessment of Persistent Organic Pollutant Exposure and Effect in Oviparous Wildlife - George P. Cobb; Tim A. Bargar; Chris B. Pepper; Don M. Norman; Pattie D. Houlis; Todd A. Anderson (Ecotoxicology, 2003)

wsp Gene Sequences from the Wolbachia of Filarial Nematodes - Chiara Bazzocchi; Wanwisa Jamnongluk; Scott L. O'Neill; Tim J.C. Anderson; Claudio Genchi; Claudio Bandi (Current Microbiology, 2000)